2013
DOI: 10.1165/rcmb.2012-0279oc
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box–1 Mediates Hyperoxia-Induced Impairment ofPseudomonas aeruginosaClearance and Inflammatory Lung Injury in Mice

Abstract: Mechanical ventilation with supraphysiological concentrations of oxygen (hyperoxia) is routinely used to treat patients with respiratory distress. However, a significant number of patients on ventilators exhibit enhanced susceptibility to infections and develop ventilatorassociated pneumonia (VAP). Pseudomonas aeruginosa (PA) is one of the most common species of bacteria found in these patients. Previously, we demonstrated that prolonged exposure to hyperoxia can compromise the ability of alveolar macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(151 citation statements)
references
References 66 publications
10
141
0
Order By: Relevance
“…For the studies involving assessment of the impact of ODSH on host resistance to Pseudomonas aeruginosa (PA), mice were anesthetized with isoflurane or sodium pentobarbital (60 mg/kg) as described previously (Patel et al, 2013) and then intranasally inoculated with PA (as indicated in figure legends) that had been prepared as outlined below. ODSH was then administered by subcutaneous injection at various timepoints post-infection.…”
Section: Animal Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…For the studies involving assessment of the impact of ODSH on host resistance to Pseudomonas aeruginosa (PA), mice were anesthetized with isoflurane or sodium pentobarbital (60 mg/kg) as described previously (Patel et al, 2013) and then intranasally inoculated with PA (as indicated in figure legends) that had been prepared as outlined below. ODSH was then administered by subcutaneous injection at various timepoints post-infection.…”
Section: Animal Studiesmentioning
confidence: 99%
“…BAL samples were prepared as described previously (Entezari et al 2012;Patel et al 2013). Briefly, after mice were euthanized, the trachea was exposed and dissected, and a 20-Gauge (Â1¼ in) catheter was inserted.…”
Section: Bronchoalveolar Lavage Fluids (Bal)mentioning
confidence: 99%
See 3 more Smart Citations